Different Pathways Leading to Integrase Inhibitors Resistance - Thierry, Eloïse; Deprez, Eric; Delelis, Olivier (Frontiers in Microbiology, 2017)
Integrase strand-transfer inhibitors (INSTIs) such as raltegravir, elvitegravir or dolutegravir, are efficient antiretroviral agents used in HIV treatment in order to inhibit retroviral integration. By contrast to raltegravir treatments leading to well-identified mutation resistance pathways at the integrase level, recent clinical studies report several cases of patients failing dolutegravir treatment without clearly identified resistance mutation in the integrase gene raising the mechanism behind the resistance. These compounds, by impairing the integration of HIV-1 viral DNA into the host DNA, lead to an accumulation of unintegrated circular viral DNA forms. This viral DNA could be at the origin of the INSTI resistance by two different ways. The first one, sustained by a recent report, involves 2-LTR circles integration and the second one involves expression of accumulated unintegrated viral DNA leading to a basal production of viral particles maintaining the viral information.